Research progress on the anti-cancer mechanisms of edible salty-flavored Chinese materia medica - Zhongqi Shen; Meng Yu; Zhenguo Wang (Frontiers in Pharmacology)
Edible salty-flavored Chinese materia medica (ESCM) refers to a category of traditional Chinese medicine (TCM) that also serve as food, characterized by their salty flavor. According to the TCM theory, ESCM can soften and disperse knots, thus potentially offering benefits for cancer prevention and treatment. With cancer remaining a major global health challenge, its primary prevention strategies, especially through dietary modification, are crucial. ESCM have recently garnered substantial attention, due to their remarkable clinical efficacy and low side-effect profile. Researches on ESCM demonstrate that they mainly function through inhibition of cancer cell proliferation, migration, and invasion, induction of cancer cell apoptosis and autophagy, regulation of the cell cycle, suppression of tumor angiogenesis, and anti-inflammatory and anti-oxidant properties. Herein, we systematically explore the well-documented ESCM’s extracts or constituents with explicit anti-cancer properties, alongside their underlying mechanisms and pathways. The review further highlights both the primary preventions and clinical trials of ESCM-related products, offering valuable insights for the development of novel dietary approaches and therapeutic interventions in cancer management.